A Rare Case of Recurrent Hematuria from Right Kidney: Radiologic Diagnosis and Treatment. (19th July 2011) - Venetucci, Pietro; Quarantelli, Mario; Iaccarino, Vittorio
Abstract : We report the case of a young woman admitted because of several and recurring episodes of macroscopic hematuria beginned after her first pregnancy. Contrast-enhanced multidetector computed tomography images showed dilated ovarian veins due to a typical pelvic varicocele. We supposed to be a right ovarian vein syndrome, a rare clinical situation characterized by an anomalous compression of the lumbar ureter by the ectasic ovarian vein; this condition may cause a chronic inflammatory stimulus above the urothelial mucosa with a following hematuria. All symptoms were solved by an endovascular treatment through the sclero-embolisation of the pelvic varicocele. After eighteen months the patient didn't present hematuria anymore and she no longer complained about her right side lumbar pain.